Non-physiologic closing of bi-leaflet mechanical heart prostheses requires a new tri-leaflet valve design. (1st April 2020) - Carrel, Thierry; Dembitsky, Walter P.; de Mol, Bas; Obrist, Dominik; Dreyfus, Gilles; Meuris, Bart; Vennemann, Bernhard; Lapeyre, Didier; Schaff, Hartzell
Abstract: Mechanical heart valve prostheses are based on older designs without changes during the last 40 years. Today, there is an unmet need for less thrombogenic mechanical prostheses. Analysis of the relationship between flow characteristics and thromboembolic complications is possible using numerical and biomolecular flow studies that have shown that the reverse rather than the forward flow is responsible for local platelet activation and thrombosis. After peak flow, leaflets experience flow deceleration and the leaflets are still widely open when the flow becomes zero. The closure of the valve starts with the onset of reverse flow. Therefore, the valve closes extremely fast with most of the leaflet traveling angle occurring in <10 ms with excessively high reverse flow velocities. The pivoting spaces, so-called "Hot Spots" should be eliminated to prevent pathologic shear stress that result in thrombosis. A novel tri-leaflet valve combines favorable hemodynamics with the durability of mechanical heart valve. This valve closes within 60 ms, much slower than bi-leaflet valves and similar to the closing mode of a tissue valve. Micro-particle image velocimetry did not show critical regions of flow stagnation and zones of excessive shear in the pivoting region suggesting low potential for thrombogenic events that should allow to avoid long-term anticoagulation. Highlights: This paper summarizes the knowledge about transprosthetic flow in mechanical heart valve and describes the advantages of a new tri-leaflet design that would allow to eliminate long-term anticoagulation